Chemistry and biology of ophiobolin A and its congeners. Issue 7 (1st April 2019) - Masi, Marco; Dasari, Ramesh; Evidente, Antonio; Mathieu, Veronique; Kornienko, Alexander
Graphical abstract: Abstract: Ophiobolin A is a fungal secondary metabolite that was found to have significant activity against apoptosis-resistant glioblastoma cells through the induction of a non-apoptotic cell death, offering an innovative strategy to combat this aggressive cancer. The current article aims to make the bridge between the anti-cancer effects of ophiobolin A and its unique reaction with primary amines and suggests that pyrrolylation of lysine residues on its intracellular target protein(s) and/or phosphatidylethanolamine lipid is responsible for its biological effects. The article also discusses chemical derivatization of ophiobolin A to establish first synthetically generated structure-activity relationship. Finally, the reported total synthesis efforts toward the ophiobolin class of sesterterpenes are discussed and identified as a fertile area for improvement in pursuit of these molecules as anticancer agents.